On the Impact of Geo-social Factors on the Employment of Graduates of Technical Universities - S. V. Lukicheva; O. Yu. Markova (Высшее образование в России)
The paper exploresthe system of factors influencing on motivation of workplace choice by graduates of technical higher education institution. The paper is based on the results of questioning of students of final courses of technical specialties. Priority factors determining the choice of the future professional activity of a young specialist are revealed. The authors state that the dominant and especially important factors are the following: geo-social factor (region, wage level, social package), career-building opportunities, gender factor, skills development, awareness about work conditions (wage level, comfort of workplace, harmful production), satisfaction of cultural needs, career guidance on previous stages, continuity of generations in the choice of profession. The purpose of the study was also to determine the interrelation between the key factors and to ensure an objective assessment of the graduates’ professional and psychological readiness to work according to the specialty chosen. Based on the research, the system-forming factors of effective employment of young specialists were determined.